Сoncept of "green" economy as condition of providing the sustainable development of the Republic of Kazakhstan (Eurasian Journal of Ecology, 2016)
Article is devoted to topical issues of development of "green" economy in the Republic of Kazakhstan. In it it is carried out the programs realized in Kazakhstan in the field of ensuring ecological safety of the country are considered and tasks of realization of Strategy of transition of Kazakhstan to "green" economy are planned.
Keywords: concept; strategy; environment; "green" economy; environment-friendly products; environmental technology.